African Youth Battling for Education How to make the most of limited resources - Luwanda, Lameck (Arusha Bookstore, 2023)
The book provides a variety of techniques and strategies to ensure that students comprehend and effectively employ concepts. Dr. Luwanda equips his readers with the means to improve their understanding and realize their complete potential by revealing tried-and-true methods such as active learning.
Keywords: Education